Development of the Eurasian Economic Union as the Integration Stage in the Eurasian (post-Soviet) Area - TAITORINA, Binur Adamovna; KASSYMBEK, Aliya; SAILIBAYEVA, Zhanel Yursunovna; KENZHIBEKOVA, Elmira Polatovna; KUTTYGALIEVA, Anarkhan Raimovna; MURATOVA, Elmira Muratkyzy (Journal of Advanced Research in Law and Economics; Vol 7 No 6 (2016): Vol 7, No 6(2016): JARLE, Volume VII, Issue 6(20), Fall 2016, 2017)
The relevance of the study stems from the need for scientific rationale of the Eurasian integration under conditions of globalization, when nation states’ opportunities to ensure consistent social and economic development and safety fairly decrease and these problems couldn’t be solved by one country. In this respect, the paper is focused on identifying or revealing a model of integration cooperation within the framework of the Eurasian Economic Union. Analytical, rather-legal and system approaches as scientific research tools, which allow examining interstate integration in a comprehensive manner, are leading methods to study the issue. It’s proved in the paper that political, legal and economic prerequisites of further forms of integration in the Eurasian area result from the very existence of the Commonwealth of Independent States and its core documents; it’s proved that the ‘Eurasian area’ category can be considered identical to the post-Soviet area in matter, which reasonable at the modern stage of integration with the trend of further change (expansion); procedural and institutional problems in the integration process management efficiency are revealed and ways to address them are suggested. The materials of the paper are relevant to develop draft laws within the framework of the Eurasian Economic Union and also to prepare conclusions and analytical materials for supranational structures.
Keywords: Eurasian Economic Union (EEU); the Commonwealth of Independent States (CIS); Collective Security Treaty Organization (CSTO); World Trade Organization (WTO)